Penerapan Internet Of Things Meeting Room Booking Integrasi Access Control Pada PT. Metadata Solusi Teknologi - Devy Ferdiansyah - Universitas BSI (Indonesian Journal of Networking and Security (IJNS), 2023)
Abstract: Mapping meeting rooms and meeting schedule management is an activity that occurs routinely in the company, for companies that have many employees and also departments or sections will certainly experience difficulties in arranging schedules and booking meeting rooms, and for certain companies security issues are priority number one, sometimes several companies use a tool-based security system in their company, where each meeting room has access control that can be opened with each employee's identity card. By using an integrated information system between the meeting room reservation system and access control, with the help of the internet network it is hoped that it will make it easier for leaders and section heads to monitor schedules for meeting room use both in the future and in progress. Key Words: Meetings, Meeting Room Booking, Access Control, IoT Abstrak: Pemetaan ruang rapat serta manajemen jadwal rapat adalah merupakan aktifitas yang rutin terjadi diperusahaan, bagi perusahaan yang memiliki banyak karyawan dan juga departemen atau bagian tentunya akan mengalamai kesulitan dalam mengatur jadwal serta pemesanan ruang rapat, dan bagi Perusahaan tertentu masalah keamanan adalah prioritas nomor satu, adakalanya beberapa perusahaan menggunakan sistem keamanan berbasis alat pada perusahaan mereka, dimana tiap ruang rapat memiliki akses kontrol yang dapat dibuka dengan kartu identitas karyawan masing-masing. dengan menggunakan sistem informasi terintegrasi antara sistem pemesanan ruang rapat dengan akses kontrol maka dengan bantuan jaringan internet diharapkan akan memudahkan pimpinan dan kepala bagian dalam memonitoring jadwal penggunaan ruang rapat baik itu di waktu yang akan datang maupun yang sedang berjalan. Kata Kunci: Meeting, Meeting Room Booking, Akses Kontrol, IoT